USP28 protects development of inflammation in mouse intestine by regulating STAT5 phosphorylation and IL22 production in T lymphocytes - Le Menn, Gwenaëlle; Pikkarainen, Keela; Mennerich, Daniela; Miroszewska, Dominika; Kietzmann, Thomas; Chen, Zhi (Frontiers in Immunology, 2024)
Introduction Ubiquitin-specific proteases (USPs), a large subset of more than 50 deubiquitinase proteins, have recently emerged as promising targets in cancer. However, their role in immune cell regulation, particularly in T cell activation, differentiation, and effector functions, remains largely unexplored. Methods We utilized a USP28 knockout mouse line to study the effect of USP28 on T cell activation and function, and its role in intestinal inflammation using the dextran sulfate sodium (DSS)-induced colitis model and a series of in vitro assays. Results Our results show that USP28 exerts protective effects in acute intestinal inflammation. Mechanistically, USP28 knockout mice (USP28-/-) exhibited an increase in total T cells mainly due to an increased CD8+ T cell content. Additionally, USP28 deficiency resulted in early defects in T cell activation and functional changes. Specifically, we observed a reduced expression of IL17 and an increase in inducible regulatory T (iTreg) suppressive functions. Importantly, activated T cells lacking USP28 showed increased STAT5 phosphorylation. Consistent with these findings, these mice exhibited increased susceptibility to acute DSS-induced intestinal inflammation, accompanied by elevated IL22 cytokine levels. Conclusions Our findings demonstrate that USP28 is essential for T cell functionality and protects mice from acute DSS-induced colitis by regulating STAT5 signaling and IL22 production. As a T cell regulator, USP28 plays a crucial role in immune responses and intestinal health.